The Effect of Audit Partner Tenure on Audit Quality - Hollins, Adam (2011)
Audit quality and the freedom which auditors give to the management of their clients in presenting financial statements has long been a concern for regulators, practitioners, and researchers. Many different ideas and studies have also been presented, with the aim of attempting to provide an explanation as to what determines the quality of a statutory audit, and how these could be applied to increase audit quality. This paper will use a number of variables to determine the effect which each one has on audit quality. To increase the validity of results, two measures of accruals will be used to test for determinants of audit quality. The first is Ball and Shivakumar (2006), and the second is Jones (1991). Both use abnormal accruals to test for the presence of earnings management, which is used as a proxy for audit quality. The presence of a significant amount of abnormal accruals represents a low audit quality, as it is deemed that the management of the client has a larger amount of discretion in presenting financial statements. This study will find that audit client size, represented by the natural logarithm of client turnover, has a significant effect on audit quality, and inidicates that larger clients may have more discretion in presenting their financial statements, indicating a lower audit quality.